Review on Soil Conservation - Prof. Shishira Kanta Behera, Prof. Sagar Chandra Senapati (International Journal of Modern Agriculture, 2020)
More than two-thirds of world population is currently under food scarcity, agricultural production does not keep pace with population growth in the developing world. The expansion of cultivable areas, the intensification of production by the introduction of high yielding varieties and the introduction of new techniques for agricultural production could lead to higher food production. However, the growth of farmland offers the least solution to the thn problem as most countries in Asia have little or no room for expansion. The grave degradation of soil and loss of soil fertility due to indiscriminate misuse of farmlands, forests and surprising land are a major problem in the areas that have already been cultivated, and are thus aggravation of the situation. The preservation of the soil used to be commonly equated with merely erosion prevention or arc restoration that already resulted in accelerated erosion. Nevertheless, modern thinking assigns the conservation of soils a. In that the central principle should be continued improving with the conservation of the available resources, a more detailed and more positive role. The conservation of soils is not just a technical issue.’Soil disintegration is the eroding of the land surface by physical powers, for example, precipitation, streaming water, wind, ice, temperature change, gravity or other normal or anthropogenic operators that scrape, isolate and evacuate soil or geographical material from one point on the earth’s surface to be saved somewhere else’.